A EPT E O CAPITAL SOCIAL: A INFLUÊNCiA DO CAMPUS PLANALTINA, NA REGIÃO DE ÁGUAS EMENDADAS | The EPT and Social Capital: the influence of Planaltina Campus in the region of Águas Emendadas (Trabalho & Educação, 2016)
In this paper, we sought to examine to what extent there was influence on the Social Capital’s stocks of the participants of the Technical Course in Agriculture, offered by Campus Planaltina the Federal Institute of Education, Science and Brasilia Technology (IFB), with a view to regional development to settlements in the Águas Emendadas region. The concept of Social Capital is associated with ideas about empowerment, decentralization and sustainable development. For this analysis, this research used a combined methodology of qualitative and quantitative. The quantitative dimension, used a survey with questions about behaviors and attitudes to identify stocks of Social Capital in the participants’s course. Then, through semi-structured interviews it have argued for is the leaders of the course participants settlements in order to see if students have become more articulate with the community to which they belong. Finally, it tried to see if the course collaborated with stocks of Social Capital, arguing teachers, through semi-structured interviews. This research concluded that, in this example, there were no increase of Social Capital’s stock among the students of the course. Therefore, it was observed that the qualifying interventions must be accompanied by research and extension projects to stimulate practices of associations and reality confrontation.___Neste artigo, buscou-se analisar em que medida existiu influência nos estoques de Capital Social dos participantes do Curso Técnico em Agropecuária, ofertado pelo Campus Planaltina do Instituto Federal de Educação, Ciência e Tecnologia de Brasília (IFB), com vistas ao desenvolvimento regional dos assentamentos da região de Águas Emendadas. O conceito do Capital Social está associado a ideias sobre empoderamento, descentralização e desenvolvimento sustentável. Para tal análise, nesta pesquisa, empregou-se uma metodologia combinada entre qualitativa e quantitativa. Na dimensão quantitativa, utilizou-se um survey com perguntas sobre comportamentos e atitudes para identificar os estoques de Capital Social nos participantes do curso. Em seguida, mediante entrevistas semiestruturadas, arguiram-se os líderes dos assentamentos participantes do curso, a fim de perceber se os estudantes se tornaram mais articulados com a comunidade à qual pertencem. Por fim, tentou-se perceber se o curso colaborou com os estoques de Capital Social, arguindo os professores, por meio de entrevistas semiestruturadas. Conclui- se que, nesse exemplo, não houve aumentos de estoques de Capital Social entre os estudantes do curso. Portanto, observou-se que as intervenções de qualificação devem estar acompanhadas de projetos de pesquisa e extensão para estimular práticas de associativismo e de enfrentamento da realidade.